Management responsibilities among dietitians: what is the level of job satisfaction and skills involved? a scoping review - Rusali, Roszanadia; Jamaluddin, Rosita; Md. Yusop, Nor Baizura; Ghazali, Hazrina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
The role of dietitians involves not solely on clinical responsibilities. Additionally, operation management responsibilities such as managing human labor, financial resources, and problem solver are the tasks that a dietitian look after. It is reported to be challenging and stressful and could affect job satisfaction levels in the working environment. This scoping review aimed to explore the job satisfaction level and skills needed among dietitians to assume management responsibilities at their workplace. This study was completed using PRISMA guidelines. Online databases (Scopus and Science Direct) were used to identify papers published from 2000 to 2019. We selected English publications from the United States, Australia, South Africa, Korea, and the United Kingdom that used job satisfaction as a primary or secondary outcome. Studies were included if they addressed dietitians who were involved in clinical work, food service, and management in their dietetic practices. Findings on existing skills, including managerial skills, communication, teamwork, and time management among dietitians with management responsibilities, have helped to enhance the job satisfaction and work quality of the dietetic profession. The findings would be useful for human resource management in the organisation, preserving the professional identity of a dietitian.